2015
DOI: 10.1097/mat.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Early Physical Therapy and Active Mobilization for Patients on Extracorporeal Membrane Oxygenation

Abstract: Physical therapy (PT) and early mobilization for critically ill patients have been popularized to decrease the length of hospital stay and to improve the quality of life after discharge. We reviewed our experience of PT and active mobilization for patients on extracorporeal membrane oxygenation (ECMO) in terms of its technical feasibility and safety. Study endpoints were safety events during PT and PT interruptions due to unstable vital signs. Of the eight patients, one patient (12.5%) had venoarterial ECMO, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 28 publications
1
61
0
6
Order By: Relevance
“…Recent expert recommendations on safety criteria for early mobilization mentioned that vasopressor use [38, 39], endotracheal intubation, RRT [38], or even life support devices like ECMO [40] should not be considered as contraindications for active mobilization. Despite that, besides the study of Pohlman et al [32] performing in-bed mobilization with maximal FiO 2 at 1.0 and vasoactive drug, no study has explored the safety of very early mobilization in critically ill patients on multiple support systems.…”
Section: Discussionmentioning
confidence: 99%
“…Recent expert recommendations on safety criteria for early mobilization mentioned that vasopressor use [38, 39], endotracheal intubation, RRT [38], or even life support devices like ECMO [40] should not be considered as contraindications for active mobilization. Despite that, besides the study of Pohlman et al [32] performing in-bed mobilization with maximal FiO 2 at 1.0 and vasoactive drug, no study has explored the safety of very early mobilization in critically ill patients on multiple support systems.…”
Section: Discussionmentioning
confidence: 99%
“…The majority were sedated and mechanically ventilated for the duration of ECMO, including all subjects that required ECMO post lung transplant. Previous studies have reported that femoral cannulation, sedation and mechanical ventilation are barriers to the early mobilization of ECMO patients, 26,27 and there are no published studies to date describing the ambulation or out of bed rehabilitation of patients with femoral venoarterial ECMO. Over half of the subjects in our study underwent femoral venoarterial ECMO and required higher sedation levels than our protocol aims.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulatory ECMO is helpful for conditioning and for assessing a patient's potential for recovery after transplantation (23). Ko and colleagues (24) showed that multiple physical therapy sessions including ambulatory ECMO are safe with the use of a mobilization screening protocol.…”
Section: Management Of Ecmomentioning
confidence: 99%